Multifunctional nanotherapeutics for treatment of ocular disease - Xia, Tian (Annals of Eye Science, 2017)
The eye is an important organ, it provides vision and it is an important component of our facial identity (1,2). There is an old saying “The eye is the window of the soul”, clear and bright eyes bring esthetic pleasure to people. Human eye is globular and consists of two main parts, the anterior and posterior segments (1,2). Although the posterior part of the eye is comfortably located in the orbit, they are delicate because its anterior segment including the cornea is exposed to the outside world, thus accessible to wear and tear. To protect and maintain the eye functions while reduce the disruptions from outside and inside the body, the eyes are equipped with defense mechanisms for both the anterior and posterior segments (1,2). For the cornea region, the eyes are associated with precorneal factors including eyelids, tear film, blinking, tear turnover, induced lacrimation and nasolacrimal drainage. Cornea itself contains multilayers of corneal epithelial cells with tight junctions, which severely limit ocular penetration of molecules (3,4). For intraocular environment (mostly the posterior parts), it contains two main barriers, blood-aqueous and blood-retina barrier with epithelial and endothelial tight junctions, which restrict penetration of molecules into the intraocular chamber (5). All these features make the eye an isolated and well-protected organ, however, they also make it hard to treat during ocular diseases (1,2).